The type-material of Arctiinae (Lepidoptera, Erebidae) described by Burmeister and Berg in the collection of the Museo Argentino de Ciencias Naturales Bernardino Rivadavia (Buenos Aires, Argentina) - Beccacece, Hernán Mario (2014)
Carlos G. Burmeister and Carlos Berg were among the most important and influential naturalists and zoologists in Argentina and South America and described 241 species and 34 genera of Lepidoptera. The Museo Argentino de Ciencias Naturales Bernardino Rivadavia (MACN) housed some of the Lepidoptera type specimens of these authors. In this study we present a catalogue with complete information and photographs of 11 Burmeister type specimens and 10 Berg type specimens of Phaegopterina, Arctiina and Pericopina (Lepidoptera, Erebidae, Arctiinae, Arctiini) housed in the MACN. Lectotypes or holotypes were designated where primary type specimens could be recognized; in some cases we were not able to recognize types. The catalogue also proposes nomenclatural changes and new synonymies: Opharus picturata (Burmeister, 1878), comb. n.; Opharus brunnea Gaede, 1923: 7, syn. n.; Hypocrisias jonesi (Schaus, 1894), syn. n.; Leucanopsis infucata (Berg, 1882), stat. rev.; Paracles argentina (Berg, 1877), sp. rev.; Paracles uruguayensis (Berg, 1886), sp. rev.